GDF10 blocks hepatic PPARγ activation to protect against diet-induced liver injury - Khrystyna Platko; Paul F. Lebeau; Jae Hyun Byun; Samantha V. Poon; Emily A. Day; Melissa E. MacDonald; Nicholas Holzapfel; Aurora Mejia-Benitez; Kenneth N. Maclean; Joan C. Krepinsky; Richard C. Austin (Elsevier, 2019)
Objective: Growth differentiation factors (GDFs) and bone-morphogenic proteins (BMPs) are members of the transforming growth factor β (TGFβ) superfamily and are known to play a central role in the growth and differentiation of developing tissues. Accumulating evidence, however, demonstrates that many of these factors, such as BMP-2 and -4, as well as GDF15, also regulate lipid metabolism. GDF10 is a divergent member of the TGFβ superfamily with a unique structure and is abundantly expressed in brain and adipose tissue; it is also secreted by the latter into the circulation. Although previous studies have demonstrated that overexpression of GDF10 reduces adiposity in mice, the role of circulating GDF10 on other tissues known to regulate lipid, like the liver, has not yet been examined. Methods: Accordingly, GDF10−/− mice and age-matched GDF10+/+ control mice were fed either normal control diet (NCD) or high-fat diet (HFD) for 12 weeks and examined for changes in liver lipid homeostasis. Additional studies were also carried out in primary and immortalized human hepatocytes treated with recombinant human (rh)GDF10. Results: Here, we show that circulating GDF10 levels are increased in conditions of diet-induced hepatic steatosis and, in turn, that secreted GDF10 can prevent excessive lipid accumulation in hepatocytes. We also report that GDF10−/− mice develop an obese phenotype as well as increased liver triglyceride accumulation when fed a NCD. Furthermore, HFD-fed GDF10−/− mice develop increased steatosis, endoplasmic reticulum (ER) stress, fibrosis, and injury of the liver compared to HFD-fed GDF10+/+ mice. To explain these observations, studies in cultured hepatocytes led to the observation that GDF10 attenuates nuclear peroxisome proliferator-activated receptor γ (PPARγ) activity; a transcription factor known to induce de novo lipogenesis. Conclusion: Our work delineates a hepatoprotective role of GDF10 as an adipokine capable of regulating hepatic lipid levels by blocking de novo lipogenesis to protect against ER stress and liver injury. Keywords: BMP-3b, ER stress, Hepatic steatosis, HFD, NAFLD, NASH, TGFβ